A note on the distortionary effects of revenue-neutral tolls in a bottleneck congestion game. (October 2016) - Janusch, Nicholas
Abstract: This note demonstrates how the redistribution of revenue from a Pigouvian policy can distort incentives and handicap the social objectives of the policy by creating a moral hazard problem. Based on the Levinson (2005) game theory model, I develop a three-player bottleneck congestion game that emulates a repeated prisoner's dilemma and derive efficient tolls. This conceptual game demonstrates the distortionary effects from a revenue-neutral toll policy with lump-sum revenue redistribution and the equity-efficiency tradeoff.